Simultaneous constraints on bias, normalization and growth index through power spectrum measurements - Di Porto, Cinzia; Amendola, Luca; Branchini, Enzo (Arxiv, 2012)
In this Letter we point out that redshift surveys can break the degeneracy between the galaxy bias, the power spectrum normalization, σ_{8,0} and the growth factor, without the need for external information by using a simple and rather general parametrization for the growth rate, the well known γ-parametrization and measuring the power spectrum at least at two different redshifts. We find that in next-generation surveys like Euclid, σ_{8,0} and γ can be measured to within 1% and 5%, respectively, while the bias b(z) can be measured to within 1-2% in each of 14 equal-width redshift bins spanning 0.7<=z<=2.